2018
DOI: 10.1007/s00586-018-5645-6
|View full text |Cite
|
Sign up to set email alerts
|

Back surface measurements by rasterstereography for adolescent idiopathic scoliosis: from reproducibility to data reduction analyses

Abstract: Data showed that RS measurements are reliable in AIS with mild severity of scoliosis. "Surface rotation" and "Side deviation" were the best descriptors of the Scoliosis angle and should be considered as key parameters when surveilling AIS with mild curves by RS surface topography. These slides can be retrieved under Electronic Supplementary Material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 20 publications
2
31
0
Order By: Relevance
“…Because ICC is more reflective of between-participant variance than within-participant measurement error [11], a population without postural deformities is more likely to have a smaller distribution of measurements (between-participant variance) than those with scoliosis or other postural deformities; thus, a lower ICC would be expected. Tabard-Fougere et al [19] and Manca et al [25] measured vertebral rotation RMS with excellent reliability in patients with adolescent idiopathic scoliosis; this higher reliability was likely because of the wider distribution of measurements in those populations (mean � 5.6 ± 2.6 and 6.8 ± 3.6, respectively). Only one other study reported ICC for this parameter in healthy participants [17], but because their sample had a wider distribution of measurements, they also reported higher reliability.…”
Section: Reliability: Intraclass Correlation Coefficientmentioning
confidence: 98%
“…Because ICC is more reflective of between-participant variance than within-participant measurement error [11], a population without postural deformities is more likely to have a smaller distribution of measurements (between-participant variance) than those with scoliosis or other postural deformities; thus, a lower ICC would be expected. Tabard-Fougere et al [19] and Manca et al [25] measured vertebral rotation RMS with excellent reliability in patients with adolescent idiopathic scoliosis; this higher reliability was likely because of the wider distribution of measurements in those populations (mean � 5.6 ± 2.6 and 6.8 ± 3.6, respectively). Only one other study reported ICC for this parameter in healthy participants [17], but because their sample had a wider distribution of measurements, they also reported higher reliability.…”
Section: Reliability: Intraclass Correlation Coefficientmentioning
confidence: 98%
“…A question specifically surveyed which sEMG variables should be considered. This is a relevant point considering the “ too many data – no data ” paradox ( 36 ), which refers to the difficulties that clinicians experience in extracting clinically meaningful parameters from newly introduced biomedical technologies (e.g., sEMG, gait analysis, back shape measurement), for which a general sentiment of distrust is often shown by clinical practitioners. Four sEMG-based parameters were indicated as important to report: ( 1 ) timing of muscle activations, ( 2 ) amplitude estimators, ( 3 ) envelope time course, and ( 4 ) indicators of signal quality/reliability.…”
Section: Discussionmentioning
confidence: 99%
“…Various parameters and indexes are drawn from the surface-topography and radiographic data that may confuse the interpretation of the results. Surface topography is usually used to detect or monitor scoliosis deformities [25,42,49,57,67,82,83,84,85,86,87,88,89,90,91,92,93,94,95,96], few publications address the physiological curvatures of the spine, lumbar lordosis and thoracic kyphosis [26,42,48,64,82,97,98,99,100]. Radiographic measurements of SVA, PT, LL, SS, or PI are based on radiographic points assessed on the full spine radiograms [72], which are inaccessible in surface measurements.…”
Section: Discussionmentioning
confidence: 99%